Using random amplification polymorphism (RAPD-PCR) markers to determine the genetic variability of some local and tissue cultured date palm Phoenix dactylifera L. cultivars. - hassan, saja; Ahmed Dinar Al-Asadi, Ahmed Dinar Al-Asadi (University of Thi-Qar Journal of agricultural research, 2025)
This study was conducted during the growing season (2024) in one of the private orchards in Nasiriyah district, the center of Dhi Qar Governorate, at longitude (46.06) and latitude (31.90) on some date palm cultivars produced by tissue culture and their counterparts grown by the offshoot method (traditional method). The aim of this study is to study the molecular characterization and determine the genetic fingerprint of the studied cultivars, which are (local Barhi and produced by tissue culture, local Balka and produced by tissue culture, local Sukkari and produced by tissue culture), in addition to the cultivars produced by tissue culture only (Khalas, Saqai and Majhool). Study molecular characters by using RAPD technique for (11) primers, And the results were analyzed for the molecular indicators using Photocapt ready-made program package, and then tree cluster analysis was conducted to distinguish between the varieties under study and draw the cluster convergence tree between the cultivars. The results showed that all the all primers used in the study (HB12, OPA12, OPB07, OPC09, OPC13, OPD10, OPD20, OPH-03, OPH-06, OPK18, and OPN-17) were efficient in determining the genetic fingerprint and finding genetic variation among the studied cultivars. The results showed that all primers gave a total number of bands (530 bands). The primer (OPH03) gave the highest number of bands (61 bands) and the number of different bands among them (51 bands), thus achieving a variation ratio of (83.60%), the highest efficiency ratio of (11.50%), and highest diagnostic power of (14.69%), while the primer (OPN17) gave lowest number of bands (31 bands), the number of different bands among them (17 bands), with contrast ratio of (54.83%), and gave lowest efficiency ratio of (5.84%). The results of the tree cluster analysis of studied cultivars and all the primers showed that studied cultivars were distributed into two groups. The first group included the cultivars (Khalas, Majhool and Saqai produced by tissue culture), while the second group included the cultivars (local Sukkari and produced by tissue culture, Barhi produced by tissue culture and local, local Balka and produced by tissue culture). The largest genetic distance was recorded by Khalas produced by tissue culture cultivar, which reached (28.8%), and thus it is the most distant genetically from the rest of cultivars, while the cultivars of second group recorded great genetic convergence, as percentage of genetic similarity between local Barhi and produced by tissue culture cultivars reached (100%), and between the local Balka and produced by tissue culture cultivars reached (100%), while the percentage of genetic similarity between the local Sukkari and produced by tissue culture cultivars reached (97%).